Fear of Missing Out as a Psychological Predictor of Problematic Internet Use in Emerging Adults: A Cross-Sectional Study - Nurul Huda; Dina Kusuma Astuti; Bella Zanuba (Asosiasi Dosen Muda Indonesia, 2026)
Excessive internet engagement has become increasingly common among young people and may develop into problematic internet use (PIU) that interferes with daily functioning. In emerging adulthood, the pressure to remain socially connected online can intensify fear of missing out (FoMO), which may undermine self-regulation and increase vulnerability to PIU. Objective: This study aims to empirically examine the effect of FoMO on PIU among individuals in the emerging adulthood stage. Methodology: A quantitative cross-sectional survey design was applied using purposive sampling. A total of 203 participants aged 18–29 years completed an online questionnaire (Google Forms). PIU was measured using an instrument based on Caplan’s (2010) dimensions, and FoMO was assessed using a scale based on Przybylski, Murayama, DeHaan, and Gladwell’s (2013) dimensions. Data were analyzed using simple linear regression. Findings: FoMO significantly and positively predicted PIU (F = 125.532; p < 0.05; R = 0.620; R² = 0.384). FoMO explained 38.4% of the variance in PIU, while the remaining 61.6% may be attributable to factors outside the model. Implications: The findings support the need for digital literacy initiatives and interventions targeting emotion regulation and self-control among emerging adults to reduce PIU risk. Future studies should incorporate additional psychosocial factors (e.g., depression, loneliness, social anxiety, and shyness) to better explain PIU and clarify underlying mechanisms. Originality: This study provides empirical evidence quantifying the contribution of FoMO to PIU specifically within an emerging adulthood sample characterized by intensive internet use, offering added value for prevention-oriented research and practice in digital mental health.